Histopathologic Study Of Esophageal Lesions Using Biopsied Data In Pathologic Departments In Tishreen University Hospitals - Ahmad, Issa (Latakia University Journal -Medical Sciences Series, 2018)
Introduction: Esophageal tumors are the most commonly malignant neoplasms, the chances of glandular esophagus carcinoma patients with Barrett's esophagus increase more than tenfold. The aims of this study are histopathologic typing, identifying the anatomical locations of esophageal neoplasms, as well as the age distribution and sex. Material and methods: we had review and examined 74 (38 males) esophageal biopsies, they were reported over three years started 2014, using light microscope in university hospitals. Results: we observed 29 tumors or intraepithelial neoplastic changes. 18 Barrett epithelium were found, eight of them have undergone dysplasia. There are 12 malignancies, eight have squamous cells and four adenocarcinoma, 10 of them were primary tumors and two secondary. The difference between the mean age of patients with Barrett's esophagus and invasive squamous carcinoma was about 14 years. Conclusion: It is useful to establish and Study the causes of dysplasia, metaplasia in esophageal epithelium, and accelerated developmental factors into invasive neoplasm. The upper gastro-intestinal endoscopy and esophageal biopsies are helpful procedures for detections the precancerous lesions, epithelial dysplasia, and malignancies دراسة آفات المريء التشريحية المرضية باستعمال معطيات خزع أقسام علم الأمراض في مستشفيات جامعة تشرين مقدمة: تعتبر أورام المريء الخبيثة من الأورام الأكثر شيوعاً، تتضاعف فرص حصول سرطانه المريء الغدية أكثر من عشرة أضعاف لدى مرضى مريء باريت. أهداف البحث: التنميط النسيجي المرضي و رصد التوضع التشريحي لأورام المريء، و كذلك التوزع العمري و الجنسي. مواد و طرق االبحث: قمنا بمراجعة و فحص 74 (38 ذكر) خزعة مريء، كانت قد سجلت في المستشفيات الجامعية بالمجهر الضوئي على مدى ثلاث سنوات بدء من 2014 ، مع رصد التوزع العمري و الجنسي. النتائج: فحصنا 29 ورم أو تغيرات ورمية ضمن الظهارة، وجدنا عدد مرضى باريت 18، لدى ثمانية منهم تغيرات ثدنية، و هناك 12ورماً خبيثاً، ثمانية حرشفية الخلايا و أربعة غدية، 10 بدئية و ورمان ثانويان. الفرق بين متوسط عمر مرضى مريء باريت و السرطانه الغازية حوالي 14 سنة. الخاتمة: من المفيد تحري عوامل ظهور الثدن في ظهارة المريء والظهارة الحؤولية، و معرفة الأسباب المسرعة لتطورها إلى ورم غاز. يعتبر التنظير الهضمي العلوي و أخذ خزع مريئية من الاجراءات المساعدة في كشف الآفات ما قبل السرطانية والتغيرات الورمية ضمن ظهارة المريء و الخباثات.